The Effect of High Fiber Consumption Patterns on Lowering Cholesterol Levels Low Density Lipoprotein: Literature Review - Heri Saputro; Lutfi Ema Rifani (Open Access Health Scientific Journal, 2021)
Background: Hypercholesterolemia can cause blockages in blood vessels and heart. Not infrequently people with hypercholesterolemia will experience myocardial infarction in the heart which leads to death. Changes in lifestyle are characterized by consuming less fiber-containing foods which have an impact on increasing LDL cholesterol levels in the blood. This study aimed to determine the effect of the application of high fiber consumption patterns on the reduction of cholesterol levels. Method: Literature review from the Google Scholar database, Pubmed published from 2010 to 2020, and manually select articles that are relevant to the research statement and use the keywords high fiber consumption patterns and hypercholesterolemia. Results: From the results of the literature review conducted, it was found that there were 10 related articles that met the criteria. Results: The results of the search are obtained by consuming a high-fiber diet (avocado, guava and dragon fruit, carrots and tomatoes, etc.) which produce nutrients and antioxidants such as anthocyanins, flavonoids, lycopene, PUFA, MUFA, niacin, fiber, vitamin C and phytosterols which can help lower LDL cholesterol levels and increase HDL. Conclusion: There is a relationship between the pattern of consumption of high-fiber foods to decrease cholesterol levels. With a high-fiber consumption pattern, it can bind bile acids and then excreted together with feces, this acid can reduce LDL cholesterol levels.